Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1103/physreve.56.r1322
|View full text |Cite
|
Sign up to set email alerts
|

Optical nonlinearity enhancement via geometric anisotropy

Abstract: We investigate the effects of geometric anisotropy on the optical nonlinearity of metal nanocrystals in a dielectric host. By invoking the effective medium approximation for anisotropic composite media, we calculate the spectral density as a function of volume fraction and anisotropy. The results show that anisotropy not only changes the spectral function substantially and thereby has a pronounced effect on the nonlinearity, but also separates the absorption peak from the nonlinearity enhancement peak so that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 7 publications
3
60
0
Order By: Relevance
“…In looking for experimental support, we find that the separation between absorption peak and nonlinearity enhancement peak proposed by one of us [90] has recently been confirmed experimentally by Guan et al [142]. In the same article by Guan et al [142], they also experimentally confirmed our theoretical prediction [54] that the peak of third order nonlinear susceptibilities shifts to longer wavelengths with an increasing applied electric field (which, during fabrication, causes metallic particles to have the form of prolate spheroid).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In looking for experimental support, we find that the separation between absorption peak and nonlinearity enhancement peak proposed by one of us [90] has recently been confirmed experimentally by Guan et al [142]. In the same article by Guan et al [142], they also experimentally confirmed our theoretical prediction [54] that the peak of third order nonlinear susceptibilities shifts to longer wavelengths with an increasing applied electric field (which, during fabrication, causes metallic particles to have the form of prolate spheroid).…”
Section: Discussionsupporting
confidence: 74%
“…Such a broad absorption band has been shown to be responsible for the enhanced nonlinear optical response as well as an attractive FOM. Yuen et al [90] pointed out that such an absorption spectrum, being related to the imaginary part of the effective dielectric constant, should equally well be reflected in the Bergman-Milton spectral representation of the effective dielectric constant [3,126,127].…”
Section: Spectral Representation For Understanding the Effective Dielmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the spherically shaped inclusions, the resonant plasmon bands for anisotropically shaped metallic nanoparticles are split for orientations along major and minor axes [147]; moreover, such particles can show a reduced plasmon relaxation time [148]. In contrast to the model discussed above (metallic core and the dielectric shell), analysis [139] is devoted to the dielectric spheroidal core and confocal metallic shell, characterized by an arbitrary ratio of the minor to major axes.…”
Section: Enhanced Bistability Of Graded Metallo-dielectric Filmsmentioning
confidence: 99%